Strain partitioning in transpressive shear zones in the southern branch of the Variscan Ibero-Armorican Arc - Dias, Rui (2003)
The Torre de Moncorvo region (NE Portugal) is a key-sector of the Autochthon Domain of the Iberian Terrane. The region experienced Variscan deformation in the southern branch of the Ibero-Armorican Arc wherein the early structures (of Upper Devonian age - D1) denotes the establishment of an heterogeneous sinistral transpressive regime. This regime was also responsible for the development of large-scale left-lateral shear zones whose direction is subparallel to major folds. Finite strains analyses were carried out in the Torre de Moncorvo region using the normalised Fry method on different strain markers: (1) distribution of detrital quartz grains in quartzite rocks of Arenigian-Lanvirnian age; (2) arrangement of oolites in discontinuous Ordovician-Silurian ironstone horizons; (3) the rotation experienced by Skolithos preserved in Lower Ordovician metasedimentary clastic rocks. The results obtained indicate the predominance slightly prolate strain ellipsoids predominate. Nevertheless, the variation of their orientation around mesoscopic folds emphasises the role of strain partitioning in transpressive regime, suggesting that different folding mechanisms were active in the course of the same deformation phase. For the studied cases, tangential longitudinal strain and flexural shear combined with regional sinistral shear seem to be the most common mechanisms of folding. Some of these three-dimensional theoretical models for strain patterns in folds could be used in other regions, where a transpressive regime is inferred.